Late Middle-early Late Albian ammonites from Ecuador - Bulot, L; Kennedy, W; Jaillard, E; Robert, E (2005)
Ammonites of the Albian genera Brancoceras, Dipoloceras, Mortoniceratoides and Neophlycticeras are described and illustrated for the first time from Ecuador. Precise stratigraphic distribution in the Rio Misahuali field section allows delineation of the Middle/Upper Albian boundary in the Oriente of Ecuador through the recognition of the Dipoloceras cristatum Zone. © 2005 Published by Elsevier Ltd.